GAMBARAN FAKTOR – FAKTOR RESIKO INFEKSI COVID-19 PADA MASYARAKAT DI DESA TAEH BARUAH KECAMATAN PAYAKUMBUH KABUPATEN LIMAPULUH KOTA, SUMATERA BARAT - Wira Heppy Nidia (Jurnal Kesehatan Tambusai, 2022)
The Covid-19 virus is a threat to the international world. Covid-19 is a group of acute respiratory diseases that cause the highest mortality in all countries. Patients infected with COVID-19 require intensive care. There are four risk factors for Covid-19 infection, namely health conditions, behavior, exposure, and social policies. This study aims to analyze the risk factors for COVID-19 infection in the community in Taeh Baruah Village, Payakumbuh District, Limapuluh Kota Regency, West Sumatra. This research is an analytic study with a cross-sectional approach. The population is 110 housewives with a quota sampling technique. The results showed that most of the respondents were aged 26-35 years and most of the respondents had a high school education level. As for the description of the risk factors for Covid-19 infection, in general, most respondents are at risk of Covid-19 infection by 55.5%. In particular, most of the behavioral sub-variables that are more at risk of COVID-19 infection in Taeh Baruah Village, Payakumbuh District, Limapuluh Kota Regency, West Sumatra. Based on the results of this study, it is hoped that the Taeh Baruah Village Apparatus and health workers will play an active role in stimulating the community to implement health protocols and provide sanctions for people who do not implement health protocols.